Pengaruh Bullying di Tempat Kerja dan Stress Kerja Terhadap Kinerja Security PT Sos Indonesia Tbk - Rahmania Rahmania; Yatimin Yatimin (Indonesian Journal of Economics Application (IJEA), 2020)
This study wanted to determine the effect of Bullying in the Workplace and Work Stress on Security Performance of PT. SOS Indonesia, Tbk at BSD City. The formulation and limitation of this research is the influence of Bullying in the Workplace and Work Stress on the Security Performance of PT. SOS Indonesia, Tbk in BSD City ”. The purpose of this research is to describe analyzing the influence, and proving the magnitude of the influence of bullying at work and job stress on the security of PT. SOS Indonesia, Tbk. The research design used is the quantitative associative method to determine the relationship between three variables, namely the X1 variable (bullying at work), the X2 variable (work stress), and the Y variable (employee performance) at PT. SOS Indonesia, Tbk at BSD City. Data collection techniques using saturated sampling. The data analysis method used in this research is multiple linear regression, multiple correlation coefficient, determination coefficient, f test, and t-test.